TÉRMINOS Y CONCEPTOS PARA LA DESCRIPCIÓN Y CARACTERIZACIÓN DE SITIOS Y CONTEXTOS CON RESTOS HUMANOS Y ELEMENTOS ASOCIADOS EN ARQUEOLOGÍA FORENSE - Estrada Moreno, Flavio Antonio (2017)
The present article proposes a series of concepts to establish a useful terminology for the description and characterization of archaeological forensic contexts produced by Human Rights Violations and common cases . It does not claim to be a finished product and this may, and should , be improved or simply discarded to the extent that its contrast with reality so determined.